Assay of Desmopressin Acetate in Nasal Spray: Development of Validated Pre Column HPLC-Fluorescence Method - Neeraj Upmanyu; Pawan Kumar Porwal (Tabriz University of Medical Sciences, 2017)
Purpose: Desmopressin acetate (DDAPV), a synthetic analogue of vasopressin, has been recommended to be used in diabetes insipidus, mild forms of hemophilia and Von Willebrand disease. The DDAPV is available for adminstration via different routes viz. oral, parenteral and nasal, however its dose is very less in case of nasal sprays (20 µg) and parenteral route (4 µg) compared to oral route (0.1 to 0.3 mg in tablet). A sensitive and selective method is needed to be developed and validated for assay of low concentrations of DDAPV in its pharmaceutical dosage form i.e. nasal spray. Methods: Simple and specific HPLC-Fluorescecne method has been proposed for the quantitation of DDAPV at nanogram level in nasal formulations for the first time. DAPV, DDAPV EP impurity-B, chlorobutanol, benzalkonoium chloride were successfully derivatised with Ortho-Phthalaldehyde (OPA) and co-eluted on a C8 (50×2.1 mm, 3.5 µm particle size, 120Å) with mobile phase composed of 0.1% trifluroacetic acid, acetonitrile and Isopropyl alcohol in ratio of 70:25:5. The emission was measured at 450nm and flow rate was 0.8ml/min. The reaction was optimized in the terms of pH, stability of formed fluorophore and time consumed during the reaction. Results: The maximal fluorescence intensity was reached when the solutions were mixed for 3 min, and remained constant for at least 30 min at 20-25ºC. The calibration curve was found linear from 50 to 5000 ng/ml with weight of 1/X2. The limit of detection was 10ng/ml and precision was less than 2.0. Conclusion: The developed HPLC-fluorescence assay method was successfully applied for quantitation of DDAPV in nasal spray. HPLC-Fluorescence method was specific, sensitive, precise and accurate for determination of DDAPV. The method was able to quantify DDAPV at 50ng/ml with sufficient accuracy and precision. The validated HPLC-Fluorescence was successfully applied.